(untitled) - Mroczkowski, Robert S. (New York, 1998)
This book connector overview, the contact interface and contact physics, contact finishes, contact spring materials. Engineering thermoplastics connectors...
Keywords: Electronic apparatus and appliances; Handbooks, manuals, etc